INFLUENCE OF ROW SPACING, SEED MATERIAL TYPE AND PLANT DENSITY ON GOWTH AND YIELD OF SUGARCANE UNDER DUAL ROW PLANTING - M B G S , KUMARI (The Journal of Research ANGRAU, 2026)
Field experiment was conducted to study influence of row spacing and plant density ongrowth and yield of sugarcane under dual row planting in plant ratoon system at RegionalAgricultural Research Station, Anakapalle, during the year 2023-24.   The experimental soil wassandy loam in texture.    Row spacings of 150 cm, 165 cm and 180 cm were tried with sett andseedling planting under three different plant densities of 100 %, 125% and 150%.  Studies onplant crop of sugarcane revealed that sugarcane yield under dual row planting of 150 cm (79.2 tha-1) and 165 cm (77.8 t ha-1) were found to be statistically similar but significantly higher over180 cm row spacing (71.9 t  ha-1).Higher cane yield of 78.2 t ha-1 recorded with seedling plantingwhich was found on par with sett planting (74.3 t ha-1). There is no significant difference in yieldwith respect to plant densities of 100 % (75.6 t ha-1) 125% (76.5 t ha-1) and 150 % (76.7 t ha-1). Inratoon crop indicated that dual row planting of 150 cm and 165 cm gave statistically on par caneyield of 67.2 t ha-1 and 64.8 t ha-1 respectively and significantly superior over cane yield at 180cm row spacing (62.8 t ha-1).  Cane yield was not influenced either due to type of planting materialor plant densities in ratoon crop of sugarcane.